Carbon dioxide emissions of plug-in hybrid electric vehicles: A life-cycle analysis in eight Canadian cities. (October 2017) - Requia, Weeberb J.; Adams, Matthew D.; Arain, Altaf; Koutrakis, Petros; Ferguson, Mark
Abstract: Plug-in hybrid electric vehicles (PHEVs) have the potential to decrease greenhouse gas emissions given certain power generation profiles. The adoption of PHEVs is associated with significant social, economic, environmental, and health benefits. However, most researchers in literature generally estimate emissions using national averages of emission data. The purpose of this paper is to address this gap. Specifically, we estimated CO2 emissions of PHEVs using a life-cycle analysis in 8 Canadian cities (Vancouver, St John's, Charlottetown, Halifax, Montreal, Toronto, Regina, and Calgary). We found that across Canada the varying electricity generation profiles affected the potential reduction benefit in life-cycle CO2 emissions. For example, 95% of the energy in the province of Alberta was generated from fossil fuels, which emited a high amount of GHGs. Consequently, Calgary (city located in Alberta) had the highest CO2 life-cycle emissions for PHEVs, where electricity generation accounted for 61% of the total emissions. Conversely, the provinces of British Columbia (BC) and Quebec (QC) used 86% and 98% clean energy, respectively. The cities evaluated in our analysis that are located in these provinces (i.e., Vancouver, BC and Montreal, QC) presented the lowest CO2 emissions from electricity generation with less than 4% of the total PHEV emissions. Our study provides insight for policy makers about direct investment in EV incentives across Canada and where these incentives could be focused. Our study results reiterated that to reduce CO2 emissions considerably, promotion of PHEVs should be integrated with renewable electricity generation options.